The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0104-14282001000300010
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Magnesium Hydroxide Produced by Magnesia Hydration as Fire Retardant for Nylon 6-6,6

Abstract: Abstract:The present work investigates the use of magnesium hydroxide, produced by magnesia hydration, as a fire retardant in polymers. The hydration was carried out in an autoclave, at temperature of 130°C for 1 hour, and the product was further submitted to cominution in a jet mill. The solids were characterized with regard to their chemical composition, particle size distribution, surface area and morphology. The performance evaluation of the hydroxide as a flame retardant for a copolymer of nylon 6-6,6 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Depending on the application aimed at, MgO hydroxylation can be either valuable or undesired and, in both cases, the knowledge of how this process occurs can be highly useful. The hydroxylation process must be efficient for the production of fertilizers [1,18], animal and human nutrition [1,27], watertreatment input [1,28], medicaments [1,27,28], fast-hardening Sorel and MgO-based cements [1,[29][30][31] and anti-flame agents for polymer composites [32][33][34] and generates particles of controllable size distribution, specific surface area and shape at competitive costs. On the other hand, it must be avoided or at least minimized in applications to refractory [10,13,14,16,[35][36][37][38][39][40] and abrasive [1] materials and optic and electronic devices.…”
Section: Production Of Different Grades Of Polycrystalline Mgomentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the application aimed at, MgO hydroxylation can be either valuable or undesired and, in both cases, the knowledge of how this process occurs can be highly useful. The hydroxylation process must be efficient for the production of fertilizers [1,18], animal and human nutrition [1,27], watertreatment input [1,28], medicaments [1,27,28], fast-hardening Sorel and MgO-based cements [1,[29][30][31] and anti-flame agents for polymer composites [32][33][34] and generates particles of controllable size distribution, specific surface area and shape at competitive costs. On the other hand, it must be avoided or at least minimized in applications to refractory [10,13,14,16,[35][36][37][38][39][40] and abrasive [1] materials and optic and electronic devices.…”
Section: Production Of Different Grades Of Polycrystalline Mgomentioning
confidence: 99%
“…8j). Studies have demonstrated this reaction can produce other compounds, as aluminum-magnesium double layered hydroxide, known as hydrotalcite [36,45,47,48], or particles of suitable morphology to act as mechanical reinforcement in polymeric composites [27,32,33,34].…”
Section: Hydroxylation Testsmentioning
confidence: 99%
“…Magnesium hydroxide has found several industrial applications typically ranging from pulp and paper production to the fields of pharmaceutical and wastewater treatment, for example. In recent years, there has been observed also a growing interest concerning the use of magnesium hydroxide powders as flame retardant and smoke‐suppressing additives to produce polymers 1, 2. The application of magnesium hydroxide as a flame retardant requires a very high quality Mg(OH) 2 powder with regard both to chemical purity and physical properties of the solid such as particle size, surface area, morphology, etc.…”
Section: Introductionmentioning
confidence: 99%
“…HM is a relevant magnesium material that has broad applicability, from flame retardant for polymers to neutralizing agent for effluent treatment. Its use as neutralizing agent is increasing in some countries because magnesium hydroxide has a high alkalinity (27%) when compared to traditional agents (calcium and sodium hydroxide) [19,20,21,22].…”
Section: Mgco3(s) → Mgo(s) + Co2(g)mentioning
confidence: 99%